The Impact of Seasonal Changes and Living Activities on Dwelling Patterns and the Form of Rural Houses (مسکن و محیط روستا)
In rural areas, housing is formed according to environmental, social and economic circumstances of rural communities. One of the criteria to classify rural housing architecture is based on climatic conditions in which the rural areas are located. However, the pattern of the activities in housing is also affected by the climate of its own. Thus, different climates would set off different activities, which occurred in the form of different types of space. Rural architecture, especially in colder regions is seasonal and affected by the activities occurring in physical attributes of the house in a way contributing further interaction with the architecture. In the rural settlements, residential spaces have been formed over the years, based on old traditions and traditional modes of spatial behavior. Each of the spaces has been emerged within rural housing conditions actively and passively by the inhabitants during a long history of gradual change and continuity to achieve a delicate homogeneity. However, today's new constructions have created great heterogeneity in rural areas due to the use of inappropriate materials and unconventional visions. This inconsistency in style and form has led to the deformity in villages and created anonymous, unreasonable, inconsistent rural settings. Therefore, understanding factors affecting the formation of rural housing and anticipating the way spaces are used is the most important issue that must be considered by any designer. This issue might be simple at first sight, but the acquisition of such knowledge requires meticulous study of activities and behavioral patterns of rural life over the years. In this paper the rural settlements are investigated architecturally and the climatic conditions of the city of Urmia is evaluated. Then the relationship between mass and space in rural settlements is further discussed. At first, some of the villages in the city of Urmia, in West Azerbaijan Province as one of the cold regions in the country are studied as prototypical models. The purpose of this paper is to examine the current activity patterns in the rural dwellings and achieving a suitable pattern for modern housing design, which fits the needs of the rural population and climatic requirements of the area. The results indicate that there is a triangular pattern and interrelationships among different seasons, housing and ongoing activities. Understanding this relationship requires a rural housing planning layout. The amount of activity in each season indicates the need for the space, which has led to the creation of spaces in a traditional manner and over the years in rural housing. According to the study, in the development of rural housing, activities patterns are tied with the temporal events suited to rural needs. Furthermore, the rural houses must be designed with a comprehensive, targeted action plan to suit the climate, culture and activities of the users. The research method is based on reviewing and the content analysis of literature and interviews with rural residents.